Correlates of burnout among professionals working with people with intellectual and developmental disabilities. Issue 10 (23rd August 2018) - Finkelstein, A.; Bachner, Y. G.; Greenberger, C.; Brooks, R.; Tenenbaum, A.
Abstract: Background: Although burnout has been recognised as an important stress‐related problem among staff working with people with intellectual and developmental disabilities (IDD), literature on the subject is limited yet emerging. The aim of this study is twofold: (1) to evaluate the level of burnout within different professions working with IDD; (2) to examine the association between socio‐demographic, professional and organisational characteristics and burnout. Method: One hundred ninety‐nine professionals working with people with IDD were enrolled in the study (66% response rate). Participants were recruited from several facilities that provide care for people with IDD of all ages, in the Jerusalem area and in other cities in central Israel. The anonymous questionnaires included valid and reliable measures of burnout, socio‐demographic variables, professional variables and organisational variables. Results: Participants' mean age was 38.3 years, and most were women. There were no significant differences in burnout levels among the different professionals. Role ambiguity, perceived overload, care‐recipient group and job involvement were significant predictors of burnout. The model explained a high percentage (46.8%) of the observed variance. Conclusions: Most of these predictors are organisational measures. These findings demonstrate that organisational variables are more significantly associated with burnout of staff working with people with IDD than the socio‐demographic factors or professional characteristics. Identifying and better understanding the specific factors associated with burnout among professionals working with IDD could facilitate unique intervention programs to reduce burnout levels in staff.